تأثير مستخلصات بعض النباتات الطبية في المعايير الفيزيولوجية للدم عند الحيوانات - فاضل هيام (Latakia University Journal -Biological Sciences Series, 2019)
تم إجراء البحث بهدف دراسة تأثير مستخلصي بذور الحبة السوداء (المائي والكحولي) في بعض المعايير الفيزيولوجية للدم عند الفئران البيضاء. وبيّنت النتائج لدى الفئران المعاملة بالمستخلص المائي والكحولي للحبة السوداء ما يلي: - زيادة معنوية في تعداد الكريات الحمر عند جميع فئران التجربة. - ازدياد تركيز الهيموغلوبين وارتفاع قيمة الهيماتوكريت عند جميع المجموعات التجريبية مقارنة مع الشاهدة. - أحدثت المعاملة بالمستخلصين (المائي 400 ملغ/كغ) و(الكحولي 400 ملغ/كغ) انخفاضاً معنوياً في العدد الكلي للكريات البيض،أما بالنسبة لصيغة الكريات البيض فقد بيّنت معدلات النسب المئوية للكريات البيض المعتدلة ارتفاعاً معنوياً عند المجموعتين المعاملتين بالمستخلص المائي(200) ملغ/كغ، والمستخلص الكحولي(200) ملغ/كغ، مقارنة مع المجموعة الشاهدة, بينما حصلت زيادة في نسبة الكريات البيض اللمفاوية وخاصة عند المجموعة المعاملة بالمستخلص المائي(400 ملغ/كغ)، أما بقية أنواع الكريات البيض (الحامضية ، الأساسية، وحيدة النوى) فقد انخفضت نسبها المئوية مقارنة بالشاهدة. The research aimed to study the effect of aqueous and alcoholic extracts of Nigella sativa L. seeds on some haematological standards at albino mice. The results showed the mice treated with aqueous and alcoholic extracts of Nigella sativa L. seeds led to: · Significant increase in red blood cell (RBC) counts of all groups. · Increased concentration of haemoglobin and haematocrit at the high value of all groups taking part in the experiment compared to control values. Treatment with aqueous and alcoholic extracts (aqueous 400 mg / kg) and (alcoholic 400 mg / kg) led to a significant decrease in the total number of white blood cells, while the formula of white blood cells (WBC) has shown a significant rise in the percentage ratio of Neutrophils when the two treatments extracts (aqueous 200 mg / kg), and (alcoholic 200 mg / kg), compared with the control group. On the other hand, there was an increase in the proportion of lymphocytes, especially when the group treated with (aqueous 400 mg / kg)), while other types of leukocytes (Eosinophils - basophils , Monocytes) decreased percentages, compared with control..